1981
DOI: 10.1159/000176496
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ovarian Hormones in the Long-Term Control of Glucose Homeostasis Glycogen Formation and Gluconeogenesis

Abstract: The effect of ovarian hormones on in vivo gluconeogenesis and glycogen deposition in liver, uterus, skeletal and cardiac muscle was studied. Ovariectomized adult female mice were treated with replacement doses of estradiol, progesterone, both hormones combined, or vehicle only for 15 weeks. Compared with intact control mice, ovariectomy increased gluconeogenesis and reduced the glycogen content of all tissues examined. Treatment with estradiol and progesterone, individually and in combination, increased tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 19 publications
4
26
1
Order By: Relevance
“…It has been reported that ovariectomy and etrogen deficiency led to decreased energy expenditure[27], increased glucose level and increased visceral adipose tissue [34,35]. Long-term estrogen deficiency may lead to reduction of insulin secretion, thus weakening the ability of controlling glucose level in ovariectomized rats [26].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ovariectomy and etrogen deficiency led to decreased energy expenditure[27], increased glucose level and increased visceral adipose tissue [34,35]. Long-term estrogen deficiency may lead to reduction of insulin secretion, thus weakening the ability of controlling glucose level in ovariectomized rats [26].…”
Section: Resultsmentioning
confidence: 99%
“…Estrogenic modulation of IIH may reflect control of sensory signaling of glucopenia, magnitude and/or duration of physiological and behavioral motor responses to hypoglycemia, and/or peripheral actions of insulin and counterregulatory hormones on target tissues. Indeed, OVX is reported to decrease glucose tolerance [13], and enhance hyperglycemic actions of glucagon and epinephrine [12], in part by suppression of hepatic glycogen production and stimulation of gluconeogenesis [14]. The current evidence that RIIH exacerbates effects of insulin in oil- but not E-implanted OVX rats implies that functions underlying glucostatic regulatory mechanisms or glucose production, storage, and/or utilization become adapted to recurring glucoprivation in the absence of circulating estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of insulin resistance show greater occurrence in men than women, even after adjusting for age and body mass index (42, 59, 80, 86). Key mechanisms that have been implicated include effects of gonadal hormone-dependent and -independent sex differences in regional adipose tissue distribution, production of cytokines and adipokines, hepatic gluconeogenesis and glycogenolysis, and glucose uptake by skeletal muscle (1, 86, 102). Sex differences in the mechanisms of dysglycemia raise a concern that diagnosis of MetSyn based on fasting glucose levels may not reliably identify women that have MetSyn and should undergo some intervention.…”
Section: Sex Differences In Obesity Co-morbiditiesmentioning
confidence: 99%